UKM Development Business Loan - Muh. Barid Nizaruddin Wajdi; Yuli Choirul Ummah; Devit Etika Sari (IJEBD (International Journal of Entrepreneurship and Business Development), 2017)
The aim for this paper is a) to identify the difficulties and problems faced by UKM in obtaining venture capital loans. b) Determining the strategy of development of UKM through increased ease of working capital credit facilities through credit channeling institution. Design/methodology/approach : This type of research is exploratory. Types of data used are data collected by primary and save a list of questions. Findings : The results are as follows: More than 50% of UKM have difficulty capital. UKM that utilize external capital sources of credit channeling institution only at 17.50%. Reason UKM have not utilized most of the credit is a factor of the policies, terms and loan interest rates are quite high.. Research limitations/implications : Location of the research done on UMKM in the district of Nganjuk. Practical implications : there are several strategies that can be done are (1) Optimizing the role KKMB in nurturing and mentoring the UKM prospect will apply for business loans, (2) promoting financing for results or venture capital, (3) enhance the role of credit guarantee institutions for UKM prospects will hit their collateral requirements. It is expected that with the implementation of the above strategies, the prospects of UKM no longer have difficulty in obtaining loans from the venture capital Credit Channeling Institutions. Originality/value : UKM provide a significant contribution to employment, amounting to 99.6 percent. Meanwhile, the contribution of UKM to Gross Domestic Product (PDB) by 56.7 percent. In the process of economic recovery of Indonesia, the UMKM sector has a strategic role and importance that can be viewed from various aspects